Insider understanding of country development: a novel application of Optimal Control Theory and Data Envelopment Analysis for benchmarking performance of Chilean and Brazilian companies - Paulo Nocera Alves Junior; Wilfredo F. Yushimito; Jorge Pereira Gude; Isotilia Costa Melo; Daisy Aparecida do Nascimento Rebelatto (The Central European Review of Economics and Management (CEREM), 2019)
Aim: If companies manage their inventory inefficiently, inventory costs can increase significantly due to shortages, overstocking, and risks. Inventory management is critical for company's success which, in turn, impacts on countries' development. This paper aims to investigate the efficiency of inventory control systems of companies from Brazil and Chile through Optimal Control Theory and Data Envelopment Analysis.Design/Research methods: Data was collected from Chilean and Brazilian companies covering different industries in which both countries are mostly dependent A new approach using OCT and DEA is applied for dealing with inventory, production, and demand in Dynamic DEA model to benchmark companies' production-inventory systems.Conclusions/findings: The results show efficient companies among evaluated industries. Such companies are related mainly to Brazilian commerce and Chilean exports. Based on findings, it was possible to identify patterns and relationship among companies and its inventory management.Originality/value of the article: This paper fills a gap in studies including demand, production, and inventory in Dynamic DEA by using OCT to forewarn unrealistic results and observing companies' behavior. Besides that, this approach is particularly useful for developing countries in this context, determining benchmarks for the most inefficient firms in each sector.Implications of the research: The results show (1) which companies should focus more on improving inventory management, (2) which companies should be used as benchmarks, and (3) it highlights the reasons of different performance of companies in each country.Limitations of the research: For future research, it is suggested including variables and analysis of social and environmental impacts.
Keywords: L21; M21; L25; 330; Data Envelopment Analysis (DEA); Optimal Control Theory (OCT); Dynamic Efficiency; Developing Countries; Inventory Control; Production-Inventory System; Benchmarking; Best Practices